2021
DOI: 10.3389/fcvm.2021.728800
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis of Hemoglobin-to-Red Blood Cell Distribution Width Ratio and Frailty in Elderly Patients With Coronary Heart Disease

Abstract: Background: Coronary heart disease (CHD) is a common chronic disease in the elderly. Frailty can accelerate the development of CHD and lead to adverse health outcomes. Risk prediction and decision-making for frailty are crucial. The peripheral hemoglobin-to-red blood cell distribution width ratio (HRR) is a novel biomarker of inflammation. Our purpose was to explore the correlation between HRR and frailty in elderly patients with CHD.Methods: This cross-sectional study evaluated 245 Chinese hospitalized patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 35 publications
2
33
0
6
Order By: Relevance
“… 32 Mohindra et al 33 showed that a proposed RDW index could potentially be an important parameter in predicting the prognosis of ischemic stroke patients. In the past two years, HRR has been widely reported as an important observation indicator of cancer prognosis.Both hemoglobin and RDW are important components of HRR, and the relationship between lower hemoglobin, higher RDW, and frailty in elderly CHD patients has been confirmed, lower HRR is associated with increased frailty risk and has a certain predictive value in elderly hospitalized patients with CHD, 11 our study is consistent with previous finding. In this study, we expounded on that finding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 32 Mohindra et al 33 showed that a proposed RDW index could potentially be an important parameter in predicting the prognosis of ischemic stroke patients. In the past two years, HRR has been widely reported as an important observation indicator of cancer prognosis.Both hemoglobin and RDW are important components of HRR, and the relationship between lower hemoglobin, higher RDW, and frailty in elderly CHD patients has been confirmed, lower HRR is associated with increased frailty risk and has a certain predictive value in elderly hospitalized patients with CHD, 11 our study is consistent with previous finding. In this study, we expounded on that finding.…”
Section: Discussionsupporting
confidence: 92%
“… 6 In recent years, a series of studies on the HRR and prognosis of cancer patients have been reported, 7–10 and a few studies on the HRR and prognosis of coronary heart disease patients have been reported. 11 So far, However, there is no relevant report studies HRR on the prognosis of severe ischemic stroke patients with AF and the correlation of adverse events. To the best of our knowledge, this is one of the first studies using the MIMIC-IV database to research the results of ischemic strokes combined with AF.…”
Section: Introductionmentioning
confidence: 99%
“…The red blood cell distribution width coefficient of variation (RDW-CV) is a quantitative estimate of the heterogeneity of red blood cell volume (RBC), commonly known as anisocytosis. There may be a possible association between elevated RDW and inflammation [ 16 , 17 , 18 , 19 ]. Inflammatory responses negatively affect red blood cell production [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There may be a possible association between elevated RDW and inflammation [ 16 , 17 , 18 , 19 ]. Inflammatory responses negatively affect red blood cell production [ 17 , 20 ]. Many of the pro-inflammatory cytokines upregulated in COVID-19, such as tumor necrosis factor-α and interleukin-1, can cause lowering of erythropoietin production [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Subsequently, Qu et al demonstrated that Hb/RDW is an independent risk factor for predicting frailty in patients with coronary heart disease. 11 They both found Hb/RDW to be a better prognostic indicator than either Hb alone or RDW by itself. This is considered that Hb/RDW combining Hb and RDW can provide more information than a single variable.…”
Section: Introductionmentioning
confidence: 97%